Modelling floating riverine litter in the south-eastern Bay of Biscay: a regional distribution from a seasonal perspective - Irene Ruiz; Anna Rubio; Ana J. Abascal; Oihane C. Basurko (Ocean Science, 2022)
Although rivers contribute to the flux of litter to the marine environment, estimates of riverine litter amounts and detailed studies on floating riverine litter behaviour once it has reached the sea are still scarce. This paper provides an analysis of the seasonal behaviour of floating marine litter released by rivers within the south-eastern Bay of Biscay based on riverine litter characterizations, drifters, and high-frequency radar observations and Lagrangian simulations. Virtual particles were released in the coastal area as a proxy of the floating fraction of riverine litter entering from rivers and reaching the open waters. Particles were parameterized with a wind drag coefficient (Cd) to represent their trajectories and fate according to the buoyancy of the litter items. They were forced with numerical winds and measured currents provided by high-frequency radars covering selected seasonal week-long periods between 2009 and 2021. To gain a better insight into the type and buoyancy of the items, samples collected from a barrier placed at the Deba River (Spain) were characterized at the laboratory. Items were grouped into two categories: low-buoyancy items (objects not exposed to wind forcing, e.g. plastic bags) and highly buoyant items (objects highly exposed to wind forcing, e.g. bottles). Overall, low-buoyancy items encompassed almost 90 % by number and 68 % by weight. Weakly buoyant items were parameterized with Cd = 0 % and highly buoyant items with Cd = 4 %; this latter value is the result of the joint analysis of modelled and observed trajectories of four satellite drifting buoys released at the Adour (France), Deba (Spain), and Oria (Spain) river mouths. Particles parameterized with Cd = 4 % drifted faster towards the coast through the wind, notably during the first 24 h. In summer, over 97 % of particles beached after 1 week of simulation. In autumn this value fell to 54 %. In contrast, low-buoyancy items took longer to arrive at the shoreline, particularly during spring with fewer than 25 % of particles beached by the end of the simulations. The highest concentrations (>200 particles km−1) were recorded during summer for Cd = 4 % in the French region of Pyrénées-Atlantiques. Results showed that the regions in the study area were highly affected by rivers within or nearby the region itself. These results couple observations and a river-by-river modelling approach and can assist decision-makers on setting emergency responses to high fluxes of floating riverine litter and on defining future monitoring strategies for heavily polluted regions within the south-eastern Bay of Biscay.